7,8-Dihydroxyflavone Attenuates Alcohol-Related Behavior in Rat Models of Alcohol Consumption via TrkB in the Ventral Tegmental Area - Li, Xin-Xin; Yang, Tao; Wang, Na; Zhang, Li-Li; Liu, Xing; Xu, Yan-Min; Gao, Qing; Zhu, Xiao-Feng; Guan, Yan-Zhong (Frontiers in Neuroscience, 2020)
Alcohol use disorder (AUD) is a ubiquitous substance use disorder in the world, of which neural mechanisms remain unclear. Alcohol consumption induces neuro-adaptations in the dopaminergic system originating from the ventral tegmental area (VTA), an important brain region for the reward function in AUD. Endogenous brain-derived neurotrophic factor (BDNF)-TrkB implicated in the development of neuroplasticity, including long-term potentiation of GABAergic synapses (LTPGABA). We previously found that ethanol blocks LTPGABA in the VTA, either in vivo or in vitro. 7,8-dihydroflavone (7,8-DHF), a BDNF-mimicking small compound, was recently found to penetrate the blood–brain barrier to mimic the biological role of BDNF-TrkB. In this study, we demonstrate that repeated ethanol consumption (including intermittent and continuous ethanol exposure) results in low expression of BDNF in rat VTA. The amount of ethanol intake enhanced significantly in rats with intermittent ethanol exposure after 72 h abstinence. Withdrawal signs emerge in rats with continuous ethanol exposure within 3 days after abstinence. Using behavioral tests, intraperitoneal injection of 7,8-DHF can reduce excessive ethanol consumption and preference as well as withdrawal signs in rats with repeated ethanol exposure. Interestingly, microinjection of K252a, an antagonist of TrkB, into the VTA blocks the effects of 7,8-DHF on ethanol-related behaviors. Furthermore, direct microinjection of BDNF into the VTA mimics the effect of 7,8-DHF on ethanol related behaviors. Taken together, 7,8-DHF attenuates alcohol-related behaviors in rats undergoing alcohol consumption via TrkB in the VTA. Our findings suggest BDNF-TrkB in VTA is a part of regulating signals for opposing neural adaptations in AUD, and 7,8-DHF may serve as a potential candidate for treating alcoholism.